Relationship of COX-2, BAX, BCL-2, Ki67, p53 Expression to Clinicopathologic Parameters and Their Impact on Prognosis in Renal Cell Carcinoma (Annals of Medical Research, 2021)
Objective: Renal cell carcinoma (RCC) is a malignancy originating from the renal cortex and is accounted for 85% of all malignant kidney tumors. Currently, tumor stage and nuclear grade are recognized as the most important determinants of prognosis in patients with RCC. Nonetheless, staging and grading do not suffice for predicting the prognosis in many patients. However, determining such patients bears importance in terms of oncology. Therefore, additional parameters are required to define the tumor behavior. In this study, we aimed to investigate the relation of Cox-2, Bax, Bcl-2, and p53 expression, as well as Ki-67 proliferation index to histopathologic parameters, and their impact on prognosis.Material and Methods: Our study included 70 RCC patients who were referred to the Pathology Department of Izmir Ataturk Teaching and Research Hospital from the First Urology Clinic between May 1998 and May 2008. The data including tumor diameter, histologic tumor type, nuclear grade, tumor stage, metastatic status, life expectancy of patients as well as staining percentages of Bax, Cox-2, Bcl-2, p53, and Ki-67 were compared.Results: In this study, no relationship was found between those markers and clinicopathologic parameters including the prognosis. Conclusion: Tumor pathologic stage showed a statistically significant predictive value for metastasis development, however, it failed to predict survival. There is a need for studies including standardized methods, larger samples, and longer follow-up periods in order to reveal effects of Cox-2, Bax, Bcl-2, P53 markers, and Ki-67 proliferation index on prognosis.
Keywords: None